An investigation of the mechanical properties and bonding mechanism of Ti/Al-laminated composites fabricated by ultrasonic consolidation. (18th February 2021) - Bo, Jiang; Xueping, Ren; Yujie, Han; Hongliang, Hou; Yaoqi, Wang
Foils such as 1100 aluminum and TC4 titanium were used as matrix materials for ultrasonic consolidation test of dissimilar metal materials, and the samples of Ti/Al-laminated composites were prepared. The effect of amplitude and static pressure on the interfacial bonding strength of Ti/Al foil was studied by adhesion test. The mechanical properties of Ti/Al-laminated composites were tested by electronic universal testing machine. The microstructure of Ti/Al foil interface was observed by transmission electron microscope. The results show that ultrasonic consolidation can achieve a good bonding interface of Ti/Al foil, and the bonding strength of the interface increases first and then decreases with the increase of static pressure, and increases monotonously with the increase of amplitude. The optimum adhesion strength is 58.08 N cm −1 . The high temperature deformation constitutive model of Ti/Al-laminated composites is established and verified. The Ti/Al interface has metallurgical bonding, and the inner microstructure of Ti/Al matrix is obviously refined. The surface of titanium foil has formed nanocrystalline.